Antennas and Propagation for Wireless Communication System - Saunders, Simon R; Aragon-Zavala, Alejandro (London Willy, 2007)
new exercises and supplementary materials to support course tutors. A vital source of information for practising and aspiring wireless communication engineers as well as for students at postgraduate and senior undergraduate levels, this book provides a fundamental grounding in the principles of antennas and propagation without excessive recourse to mathematics. It also equips the reader with practical prediction techniques for the design and analysis of a very wide range of common wireless communication systems
"Companion Website"
12
Keywords: Computer peripherals; Information networks; Radio -- Receivers and reception; Telecommunication; Wirreless communication systems